Structural and Optical Investigation of Aluminium-Lithium- Borate Glasses - Singh, Gurinder Pal; Kaur, Parvinder; Kaur, Simranpreet; Arora, Deepawali; Singh, D. P. (Asian Review of Mechanical Engineering, 2012)
Glass samples of compositions xAl O -(30- ) 2 3 x Li CO –70B O with x varying from 0 to 8% mole fraction are 2 3 2 3 prepared by melt quench technique. Decrease in the band gap from 3.12 to 2.91 eV for lithium borate glasses with an increase in the Al O content has been observed and discussed. The 2 3 FTIR spectral studies have pointed out the conversion of structural units of BO to BO . Due to the formation of BO and 3 4 4 AlO units, changes in the atomic structure with Al O 6 2 3 composition are observed and discussed.